LAW-LANGUAGE: THE CHALLENGE OF THE CAVEAT ‘WHENEVER REASONABLY PRACTICABLE’ IN LANGUAGE POLICIES - Montle, Malesela; Kekana, Tebogo Johannes (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
The challenge of escape clauses in various policies has been a longstanding issue for policy scholars worldwide. This challenge is also prevalent in South African institutions, particularly in their language policies. This article reports on the findings of a desk-based investigation into the escape clause "whenever practicable" as found in various language policies. A textual analysis of language policies from specifically selected institutions was conducted. The research argues that language planning agencies in these institutions have inadvertently or deliberately included escape clauses as a mechanism to allow for flexibility in case of difficulties in implementing certain provisions of the policies. Data were collected from the language policies of seven universities and three government departments using convenient sampling. Discourse analysis was employed to analyze the data, focusing on the linguistic meaning of the selected extracts containing escape clauses. The analysis revealed several key findings: the language policies examined confirmed the presence of various escape clauses expressed in different ways; these escape clauses contribute to the lack of implementation of these language policies; and the absence of non-compliance clauses also contributes to the lack of implementation. The findings clearly indicate that escape clauses are a critical pivot around which the escape mechanisms in these selected language policies revolve. Therefore, we argue that the use of escape clauses should be limited and highly regulated.